1990
DOI: 10.1002/bip.360290206
|View full text |Cite
|
Sign up to set email alerts
|

Small‐angle neutron scattering study of the structure of protein / detergent complexes

Abstract: Small-angle neutron scattering (SANS) was used to study the structure of protein/sodium dodecylsulfate complexes. Two water soluble proteins, bovine serum albumin (BSA) and ovalbumin (OVA), were used. The protein concentration was kept constant at 1 wt %, and protein/detergent wt ratio varied between 1/1, 1/1.5, 1/2 and 1/3. Absolute intensities of SANS distributions were analyzed by a fractal model. Analyses of large Q portions of SANS distributions established that sodium dodecylsulfate (SDS) molecules bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
123
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 17 publications
9
123
0
Order By: Relevance
“…and can be obtained from the Fourier transform of equation (1) (Chen & Teixeira, 1986;Guo et al, 1990), where R is the radius of the primary particles. The modulus of the scattering vector Q = (4 / ) sin( /2) is defined by the scattering angle , and the wavelength of the X-rays .…”
Section: Saxs Modelmentioning
confidence: 99%
“…and can be obtained from the Fourier transform of equation (1) (Chen & Teixeira, 1986;Guo et al, 1990), where R is the radius of the primary particles. The modulus of the scattering vector Q = (4 / ) sin( /2) is defined by the scattering angle , and the wavelength of the X-rays .…”
Section: Saxs Modelmentioning
confidence: 99%
“…Information concerning the structure of protein-surfactant complexes has been derived from rheological (Reynolds and Tanford 1970b), spectroscopic (Das et al 1998;Gelamo et al 2002), electrophoretic (Gelamo et al 2002), binding (Jones 1975;Tanford 1980), and scattering studies (Chen and Teixeira 1986;Guo et al 1990). Several models have been proposed for the structure of protein-surfactant complexes in SDS over its critical micelle concentration (CMC): (1) a correlated "necklace and bead" model in which clusters with a micelle-like structure are stabilized by protein ( Fig.…”
mentioning
confidence: 99%
“…Several models have been proposed for the structure of protein-surfactant complexes in SDS over its critical micelle concentration (CMC): (1) a correlated "necklace and bead" model in which clusters with a micelle-like structure are stabilized by protein ( Fig. 1; Shirahama et al 1974;Guo et al 1990;Turro et al 1995); (2) "rod-like" prolate elliposidal surfactant aggregate with a semi-minor axis of ∼18 Å, corresponding to the surfactant chain length (Reynolds and Tanford 1970b;Tanford 1980); and (3) a flexible capped helical cylinder micelle with the protein wrapping around the micelle (Lundahl et al 1986). A small-angle neutron scattering study of BSA and ovalbumin complexes with SDS led to the conclusion that a necklace and bead structure, composed of protein-surfactant aggregates, accounted for the scattering behavior of these systems (Chen and Teixeira 1986;Guo et al 1990), which was confirmed by NMR experiments by Turro et al (1995).…”
mentioning
confidence: 99%
“…The structure of protein-surfactant complexes has been studied for many years using several low molecular mass globular proteins such as bovine serum albumin, lysozyme, and others by means of several spectroscopic techniques such as UV-visible absorption (5), fluorescence and circular dichroism (12,(15)(16)(17), small angle neutron scattering (18,19), small angle x-ray scattering (SAXS) (20), light scattering (21), and other tensiometric and viscosimetric physicochemical techniques (22) as well as isothermal titration calorimetry and differential scanning calorimetry (23,24).…”
mentioning
confidence: 99%